Respuesta :

Answer:

Please check the explanation.

Step-by-step explanation:

The midpoint (a, b) of line joining points (x₁, y₁) and (x₂, y₂)

a = x₁ + x₂ / 2

b = y₁ + y₂ / 2

Given that the midpoint of AB is (4, -3).

i.e. (a, b) = (4, -3)

Given that A has coordinate (1, 5).

i.e. (x₁, y₁) = (1, 5)

We have to determine the coordinates of B.

i.e. (x₂, y₂) = B

Thus,

4 = (1 + x₂)/2

(1 + x₂) = 4 × 2

1 + x₂ = 8

x₂ = 7

and

-3 = (5 + y₂)/2

(5 + y₂) = -3 × 2

5 + y₂ = -6

y₂ = -11

so (x₂, y₂) = (7, -3) = B

Thus, the coordinates of B = (x₂, y₂)  = (7, -3)

Therefore,

x₂ + y₂ = 7 + (-3)

          = 7 - 3

          = 4

Hence, the value of x₂ + y₂ = 4